Accident proneness research in the occurrence, causation, and prevention of road accidents, - Shaw, Lynette; Sichel, Herbert S. (International series in experimental psychology, 1971)
Accident Proneness: Research in the Occurrence, Causation, and Prevention of Road Accidents deals with concept of accident proneness. The concept has had a checkered career, from the early British work whose high scientific standard has been universally acknowledged, through a period when the concept was extended beyond the sound basis which had been laid, to a period of reaction when doubt was thrown on the very existence of such a notion. The book examines in detail the arguments brought forward by the proponents of both sides, and, more importantly, studies in detail the facts and figures q.